Operational efficiency of combine harvesters on different field size in the selected area of Bangladesh (Bangladesh Rice Journal, 2025)
The length and width of the rice field play a crucial role in the performance of the combine harvester. Effect of field size (length of the field) on field performance of head feed (Kubota PRO588I-G and Yanmar AG600A) and whole feed (Yanmar YH700 and FM World WM 4LZ-4.0EA) combine harvesters were assessed in both irrigated dry season 2021-22 and non-irrigated wet season 2022 in two different regions of Bangladesh. Five levels of field length, i.e.  ≤30m (L1), 30-40m (L2), 41-50m (L3), 51-60m (L4), and 61-70m (L5), were chosen to investigate forward speed, theoretical field capacity, effective field capacity, and field efficiency. The results revealed that all the performance parameters increased significantly with the increase of field length for all types of combine harvesters in both seasons. In the irrigated dry season, forward speed varied from 1.4 to 3.4 and 4.0 to 6.7 km/h of the head feed and whole feed combine harvester, respectively with the field length L1 to L5, whereas significantly higher forward speed was observed for whole feed combine harvesters. Contrary, the field efficiency varied from 20 to 64 and 23 to 65% of the head feed and whole feed combine harvesters, respectively with the field length L1 to L5. In the non-irrigated wet season, forward speed varied from 3.1 to 4.5 and 3.7 to 4.8 km/h of the head feed and whole feed combine harvesters, respective with the field length L1 to L5. Contrary, the field efficiency varied from 40 to 80 and 38 to 76% of the head feed and whole feed combine harvesters, respectively with the field length L1 to L5. The field length for the studied combine harvester should not be less than 41-50 m to obtain more than 50% field efficiency of the machine in both the irrigated dry and non-irrigated wet season in Bangladesh.Bangladesh Rice J. 27(2): 67-82, 2023